2003
DOI: 10.1103/physrevd.67.114009
|View full text |Cite
|
Sign up to set email alerts
|

Sum rules in the heavy quark limit of QCD

Abstract: In the leading order of the heavy quark expansion, we propose a covariant method, within the OPE and the trace formalism, that allows to obtain, in a systematic way, Bjorken-like sum rules for the derivatives of the elastic Isgur-Wise function ξ(w) in terms of corresponding Isgur-Wise functions of transitions to excited states. To illustrate the method, we give a simultaneous derivation of Bjorken and Uraltsev sum rules, with generalizations of the latter for w = 1. On the other hand, we obtain a new class of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
97
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(98 citation statements)
references
References 23 publications
1
97
0
Order By: Relevance
“…The main general reason is that the shape of the latter is linked to the determination of the CKM matrix element |V cb | through the exclusive processes B → D ( * ) ℓν. As pointed out in [3], a more quantitative reason is that, beyond the first derivative, higher derivatives will play a non-negligible role at the edge of the phase space, at high w, in the region where the data are presently rather precise, and will become more and more precise in the near future.…”
Section: Lpt Orsay 04-14mentioning
confidence: 99%
See 4 more Smart Citations
“…The main general reason is that the shape of the latter is linked to the determination of the CKM matrix element |V cb | through the exclusive processes B → D ( * ) ℓν. As pointed out in [3], a more quantitative reason is that, beyond the first derivative, higher derivatives will play a non-negligible role at the edge of the phase space, at high w, in the region where the data are presently rather precise, and will become more and more precise in the near future.…”
Section: Lpt Orsay 04-14mentioning
confidence: 99%
“…Using the OPE in the heavy quark limit of QCD, new Bjorken-like sum rules (SR) have been obtained [1,2,3]. It has been shown that the Isgur-Wise (IW) function ξ(w) is an alternate series in powers of (w − 1), and lower bounds have been found on the absolute magnitude of its derivatives.…”
Section: Lpt Orsay 04-14mentioning
confidence: 99%
See 3 more Smart Citations